PHYTOCHEMICAL STUDY FROM THE AERIAL PARTS OF Pavonia malacophylla (MALVACEAE) AND EVALUATION OF ITS ANTIMICROBIAL POTENTIAL - Janderson Barbosa Leite de Albuquerque; Otemberg Souza Chaves; Wallace Amorim Machado de Queiroz; Bárbara Fernandes Araújo Rodrigues; Diégina Araújo Fernandes; Fábio Correia Sampaio; Maria de Fátima Agra; Maria de Fátima Vanderlei de Souza (Química Nova)
Pavonia malacophylla (Link & Otto) Garcke (Malvaceae sensu lato), commonly known as “malva-rosa” or “malva-veludo”, is traditionally used to treat flu, cough, and heart pain. The crude ethanolic extract (CEE) of P. malacophylla was obtained through maceration with ethanol, concentrated using a rotary evaporator, and subjected to vacuum liquid chromatography with silica gel 60 as the stationary phase. Hexane, ethyl acetate, and methanol were used as mobile phases in increasing polarity gradients, yielding nine fractions. Chromatographic fractionation led to the isolation and identification of 18 compounds, including one alcohol, three steroids, three triterpenes, four pheophytins, six flavonoids and one phenolic acid. Among these, compounds 1 (decanol), 4a (α-amyrin), 4b (β-amyrin), 11 (5,8-dihydroxy-7,4’-dimethoxyflavone) and 16 (methyl-4-hydroxycinnamate), were identified for the first time in the genus Pavonia. Microbiological assays of the CEE, fractions, and isolated compounds were conducted against Escherichia coli, Candida albicans, and Staphylococcus aureus, demonstrating antimicrobial activity at concentrations ranging from 250 to 400 µg mL-1.